Life Satisfaction and Character Strengths in Women With Breast Cancer: Zest and Hope as Predictors. - Soria-Reyes, Lorena M.; Cerezo-Guzmán, María Victoria; Molina, Paula; Blanca-Mena, María José (Integrative Cancer Therapies, 2023)
Background:Empirical evidence shows that life satisfaction is positively related to character strengths, and although this association has been observed in different populations, it is scarce in breast cancer patients. This study analyzes the relationship between character strengths and life satisfaction in Spanish women diagnosed with breast cancer. Methods:A sample of 117 women completed the Satisfaction with Life Scale (SWLS) and the Spanish version of the VIA Inventory of Strengths (VIA-IS). Correlation analysis and regression modeling were performed to determine which strengths predict life satisfaction. Results:The results of the correlation analysis showed that 15 strengths were positively and significantly associated with life satisfaction, with the highest correlations corresponding to zest, hope, curiosity, social intelligence, love, gratitude, and judgment. Regression modeling indicated that of these, zest and hope were key strengths for predicting life satisfaction. Conclusions:These findings suggest that intervention programs based on the development of zest and hope could help to improve life satisfaction and, therefore, the psychological well-being of women with breast cancer.
Keywords: Mamas - Cáncer; Bienestar social; Optimismo; Hope; Zest; Virtues; Satisfaction with life; Breast cancer